PENGARUH GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI HUBUNGAN MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN - Kristanti, Emy Wahyu; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test: (1) the influence of profit management to the firm value, (2) the influence of GCG to the firm value and (3) the influence of GCG as the moderate correlation of earnings management to the firm value. In this research the earnings management is measured by using discretionary accrual and by applying Modified Jones Model, firm value is measured by using Tobinâs q ratio, and GCG is measured by using factor score in Wahidahwatiâs research (2012). The population of this research is manufacturing companies which are listed in Indonesia Stock Exchange in 2010-2014 periods. The sample collection technique has been done by using purposive sampling, and 305 sample companies sample during 5 years have been obtained. This research has been done by using multiple linear regressions analysis technique and by applying the interaction method. The result of this research shows that: (1) the earnings management does not have any influence to the firm value. (2) GCG has positive influence to the firm value. (3) GCG as the moderate variable does not able to weaken the influence of earnings management to the firm value.Keywords: Earnings Management, Firm Value, GCG.